EFEKTIVITAS MODEL PEMBELAJARAN TEAMS ASSISTED INDIVIDUALIZATION (TAI) TERHADAP KEMAMPUAN BERHITUNG DALAM PEMBELAJARAN MATEMATIKA SISWA KELAS II SD MUHAMMADIYAH AMBARBINANGUN (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The goal of this research is to find out how well second graders' arithmetic numeracy skills improved after using the Teams Assisted Individualization (TAI) approach to learning. Students' lack of proficiency in mathematics must be immediately addressed. One way to address this is to use a learning model that is ideal for improving students' numeracy abilities. In this work, a quasi-experimental approach was used in conjunction with a non-equivalent control group design. Second graders from Muhammadiyah Ambarbinangun Elementary School were all involved. Data was gathered using a pretest and posttest administered using purposive sampling. Class A was used as the control group, and Class B as the experimental group. The total number of students included in the sample was 64. An Independent Sample T-test using SPSS, in addition to prerequisite tests for normalcy and homogeneity, were utilized to assess the data. After comparing each class's average pre- and post-test results, we discovered several discrepancies. The control group averaged 49.92 on the pretest, while the experimental group averaged 48.82. In contrast to the control group's posttest score of 58.98, the experimental class achieved a score of 75.70. The significance value (Sig. 2-tailed) of 0.000 < 0.005 from the research data analysis indicates a significant difference in the average posttest scores between the control and experimental classes. Thus, it can be concluded that the Teams Assisted Individualization (TAI) learning paradigm enhances the numeracy ability of second graders.